Bad dreams and other stories - Hadley, Tessa (Harper, an imprint of HarperCollinsPublishers, 2017)
The award-winning author of The Past once again "crystallizes the atmosphere of ordinary life in prose somehow miraculous and natural" (Washington Post), in a collection of stories that elevate the mundane into the exceptional. The author of six critically acclaimed novels, Tessa Hadley has proven herself to be the champion of revealing the hidden depths in the deceptively simple. In these short stories it's the ordinary things that turn out to be most extraordinary: the history of a length of fabric or a forgotten jacket. Two sisters quarrel over an inheritance and a new baby; a child awake in the night explores the familiar rooms of her home, made strange by the darkness; a housekeeper caring for a helpless old man uncovers secrets from his past. The first steps into a turning point and a new life are made so easily and carelessly: each of these stories illuminate crucial moments of transition, often imperceptible to the protagonists. A girl accepts a lift in a car with some older boys; a young woman reads the diaries she discovers while housesitting. Small acts have large consequences, some that can reverberate across decades; private fantasies can affect other people, for better and worse. The real things that happen to people, the accidents that befall them, are every bit as mysterious as their longings and their dreams. Bad Dreams and Other Stories demonstrates yet again that Tessa Hadley "puts on paper a consciousness so visceral, so fully realized, it heightens and expands your own. She is a true master" (Lily King, author of Euphoria).